Structure optimization of large-solid-core photonic crystal fibers based on Ge\(_20\)Sb\(_5\)Se\(_75\) for optical applications - Ngoc Vo Thi Minh; Danh Nguyen Thanh; An Nguyen Manh; Tham Tran Hong; Van Thuy Hoang; Lanh Chu Van; Le, Van Hieu (Communications in Physics, 2023)
This paper presents a new design of Ge20Sb5Se75 large-solid-core photonic crystal fiber (PCF) with a 1st-ring-removed square lattice. Using the full vector finite element method for anisotropic perfectly matched layers, we numerically examine the dispersion characteristics of the PCF in the wavelength range spanning from 1.5 µm to 6.0 µm. The results reveal that photonic crystal fibers exhibit a variety of dispersion properties, including all-normal and anomalous dispersion, featuring one or two zero dispersion wavelengths (ZDWs). We propose two designs with optimal dispersion characteristics based on our numerical simulations. These designs have small lattice constants (Ʌ = 1.0 µm; Ʌ = 1.5 µm) and low fill factors (d/Ʌ = 0.3; d/Ʌ = 0.35). Furthermore, these selected fibers offer high nonlinearity and low confinement loss, making them excellent candidates for a wide range of optical applications.